"If Torture Is Wrong, What About 24?" Torture and the Hollywood Effect. (November 2018) - Kearns, Erin M.; Young, Joseph K.
Since 9/11, entertainment media has focused on depictions of terrorism and counterterrorism. How do dramatic depictions of counterterrorism practices—specifically torture—affect public opinion and policy? Using a mixed within-subjects and between-subjects experimental design, we examine how framing affects support for torture. Participants ( n = 150) were randomly assigned to a condition for dramatic depictions showing torture as (a) effective, (b) ineffective, or (c) not present ( control ). Participants who saw torture as effective increased their stated support for it. Participants who saw torture—regardless of whether or not it was effective—were more likely to sign a petition on torture. We discuss the policy implications of our findings on how framing affects opinion and action regarding torture.